Elite and excellence in the perspective of adolescents and their peers at exclusive schools - Krueger, H.-H.; Kessler, C.; Otto, A.; Schippling, A. (Zeitschrift für Erziehungswissenschaft, 2014)
Against the backdrop of the recent political discourse on elite and excellence in the German education system, this paper examines how such constructions manifest themselves in programmatic concepts of schools and in the orientations of their pupils and their peers. They are reconstructed on the basis of a qualitative research project on educational careers of young people. This paper focuses on pupils and their peers at an elite school of sports and an international school. Firstly, the state of research on those types of school as well as on educational careers of their pupils will be presented. Secondly, the theoretical reference points and the methodological design of the study will be introduced. At the core of the paper is the analysis of the education related orientations of selected cases of young people and their peers: How do they position themselves towards elite and excellence in their individual and collective orientations and how is this relevant for processes of distinction and coherence building in the groups? In the resuming part of the paper, the results will be summarised and related to the state of research and the scientific discourse on elite and excellence.